Young Learners’ Language Learning Strategies in Learning Speaking - Yeni Nurwahidah (Journal of English Education Program (JEEP), 2018)
This study is aimed at analyzing what kinds of language learning strategies are used and mostly used by young learners in learning speaking at the fourth grade of an elementary school in Ciamis. Furthermore, the qualitative method used by the writer was case study to identify the used of language learning strategy in learning speaking. In this case, the writer used purposive sampling as the sampling technique to take the sample. All the students at class IV were choosen as the sample of this study cosisted of 20 students. This study used observation and questionnaire as the research instruments. The result from the observations were some strategies are used by young learners they are memory, cognitive, compensation, metacognitive, and affective. Meanwhile, from the Strategy Inventory for Language Learning (SILL) showed that the students at the fourth grade of MIS Utama Ciamis was low. It means that generally, the used of learning strategies when the students learning speaking is less. From the questionnaire, there was metacognitive strategy are mostly used by the students in learning speaking. Based on these findings, this  study concludes that the students in the age of young learners learned English more slowly, and  they used metacognitive strategy more than other strategy. Hence, the teacher must be slow and clear in giving explanation about the material in teaching and learning process.